Imaging Patterns in Depressive Disorder: A Comprehensive Magnetic Resonance Imaging Assessment of Brain Anatomy - Nadhrati Surura, Hedya; Yuslila, Ewi; Amris, Fazil; Al Bukhari, Al Bukhari; Fitria, Syukria (Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh, 2025)
This literature examines the significant role of magnetic resonance imaging (MRI) in the diagnosis and evaluation of the anatomical features of the brain in patients with depressive disorders. A comprehensive understanding of psychiatric mechanisms through imaging techniques facilitates the development of more effective strategies for managing individuals with depression. Reference sources come from international journals obtained systematically from reputable databases; PubMed, Science Direct and Scopus with a range of publication years from 2020 to 2024. The keywords used in this literature searching process are